A arbitragem como meio de resolução de conflitos no Agronegócio - Rocha, Vitor Hassan Lima (Brasil, 2024)
The objective of this research was to analyze the institution of arbitration as a method of resolving conflicts in the context of agribusiness and in all sectors related to it; especially in conflicts involving available property rights, recognized by specific legislation. The methodology used in this research was the deductive method; As for the means, the research was bibliographic, using doctrine and legislation. As for the purposes, the research was qualitative. It is concluded that arbitration represents an effective method in the management of legal relations in agribusiness, highlighting a difference in relation to speed and accurate technical analysis compared to the Brazilian Judiciary and, it also offers the parties the opportunity to choose arbitrators with specific knowledge in the sector, which ensures more appropriate and informed decisions.